Mantonico and Pecorello Grape Seed Extracts: Chemical Characterization and Evaluation of In Vitro Wound-Healing and Anti-Inflammatory Activities - Gabriele Carullo; Fabio Sciubba; Paolo Governa; Sarah Mazzotta; Luca Frattaruolo; Giorgio Grillo; Anna Rita Cappello; Giancarlo Cravotto; Maria Enrica Di Cocco; Francesca Aiello (MDPI AG, 2020)
The winemaking process produces a huge number of pomaces that generally are used for energy purposes. Further valuable applications such as health-promoting properties are still under investigation. The seeds of the white berries of Mantonico and Pecorello cv. were extracted in a Soxhlet apparatus, using n-hexane and chloroform as solvents. Extracts were characterized by NMR and GC-MS analyses. They were assayed in vitro as wound healing and anti-inflammatory agents in HaCaT and RAW 264.7 cell lines, respectively. n-hexane Mantonico extract resulted in the most interesting wound healing sample, while n-hexane Pecorello, containing a good number of carotenoids, resulted in a good anti-inflammatory candidate. These preliminary findings underlined the benefit of grape seed extracts valorization due to their health-promoting properties.